(untitled) (Research, Society and Development, 2023)
This research addresses the question: What challenges does climate change present in the field of veterinary practice? Addressing this issue is important because it reflects a critical connection in animal health and environmental sustainability. The literature review involved a search in the Web of Science’s core collection of publications at the intersection of climate change and veterinary practice and an extended search on Google Scholar focused on Latin America, resulting in approximately 400 manuscripts. Most of the literature is concentrated in developed countries, while there is a scarcity of research in developing countries. The volume of manuscripts on this theme grew until 2021, but since then it has begun to decline. The findings indicate an urgent need for research in developing countries, but also in ways to engage veterinary practice in the stewardship of climate change. Additionally, it is recommended to include material on climate change in the curriculum of veterinary programs. Future research should focus not only on developing countries, where the economy relies heavily on animals, but also on exploring and promoting ways to engage veterinary practice in the responsible and proactive management of climate change.